2020
DOI: 10.3389/fspas.2020.00016
|View full text |Cite
|
Sign up to set email alerts
|

Collisionless Shocks as a Diagnostic Tool for Understanding Energetic Particle Transport in Space Plasmas

Abstract: We study the transport of energetic particles accelerated at three different shock events observed in the solar wind by the ACE spacecraft. We consider particle propagation for a quasi-parallel, an oblique, and a quasi-perpendicular shock. The transport regime is deduced from the shape of the energetic particle profiles upstream of the shock, and for these events the profiles are well-fitted by power-laws with slope β. This corresponds to a superdiffusive transport with the anomalous diffusion exponent α = 2 −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…This means that the flux of those particles is substantially reduced under those conditions, and this promotes the observations of flat spectra upstream of the shocks. Note that the observed reduction of the flux involves energy channels below about 400-600 keV, which are the channels where the upstream energetic particle fluxes are frequently seen to be overlapped (see also Zimbardo et al 2020, for the θ Bn dependence).…”
Section: Discussion Of the Velocity-filter Conditionmentioning
confidence: 95%
See 1 more Smart Citation
“…This means that the flux of those particles is substantially reduced under those conditions, and this promotes the observations of flat spectra upstream of the shocks. Note that the observed reduction of the flux involves energy channels below about 400-600 keV, which are the channels where the upstream energetic particle fluxes are frequently seen to be overlapped (see also Zimbardo et al 2020, for the θ Bn dependence).…”
Section: Discussion Of the Velocity-filter Conditionmentioning
confidence: 95%
“…An ion foreshock and ultra-low-frequency waves can also be detected upstream of quasi-perpendicular IP shocks (Kajdič et al 2012;Blanco-Cano et al 2016). However, it should be noted that enhanced levels of magnetic fluctuations upstream of quasi-parallel IP shocks are not always observed (Blanco-Cano et al 2016); for instance, in a recent study Zimbardo et al (2020) found that the magnetic power at the scales corresponding to energetic particle resonance was approximately constant from upstream to downstream for three IP shocks with different values of θ Bn . Therefore, the conditions under which self-generated turbulence are actually found need to be better understood.…”
Section: Introductionmentioning
confidence: 98%